2011
DOI: 10.2174/187152011796817655
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hyaluronan Synthase-3 Decreases Subcutaneous Colon Cancer Growth by Increasing Apoptosis

Abstract: Hyaluronan (HA) and hyaluronan synthases (HAS) have been implicated in cancer growth and progression. We previously have shown that HAS3 and HA mediate tumor growth in SW620 colon cancer cells, but the mechanism remains poorly understood. In addition, the effect of HAS3 inhibition on tumor growth with other cells lines has not been explored. We therefore hypothesized that inhibition of HAS3 in highly tumorigenic HCT116 colon cancer cells would decrease tumor growth and that the underlying mechanism would invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…The average size of BxPC-3 HAS3 tumors was 1,905 mm 3 on day 15 after initiation of vehicle treatment while the average size of BxPC-3 tumors was 820 mm 3 (Figures 3(a) and 3(c)). This is consistent with the report that HAS3 overexpression enhances extracellular matrix deposition and tumor growth of prostate cancer cells [45] and that metastatic colon cancer cells have upregulated levels of HAS3 [52]. HAS3 protein level is higher in human ovarian cancer than in normal ovary, and the amount of HAS3-positive cancer cells correlates with hyaluronan accumulation in the stroma [44].…”
Section: Resultssupporting
confidence: 91%
“…The average size of BxPC-3 HAS3 tumors was 1,905 mm 3 on day 15 after initiation of vehicle treatment while the average size of BxPC-3 tumors was 820 mm 3 (Figures 3(a) and 3(c)). This is consistent with the report that HAS3 overexpression enhances extracellular matrix deposition and tumor growth of prostate cancer cells [45] and that metastatic colon cancer cells have upregulated levels of HAS3 [52]. HAS3 protein level is higher in human ovarian cancer than in normal ovary, and the amount of HAS3-positive cancer cells correlates with hyaluronan accumulation in the stroma [44].…”
Section: Resultssupporting
confidence: 91%
“…Of these, 9 were down-regulated after knocking out LSD1, and the remaining 19 were up-regulated (Table 1 and Figure 5C). Interestingly, among these genes, 4 genes, including ADM [41], DKK1 [42], HAS3 [43] and SMURF2 [44], have been reported to be involved in colorectal tumorigenesis. Thus, we tried to find clues from these four for exploring the role of LSD1 in colorectal tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Hyaluronan synthase 3 (HAS3) is one of the three HAS isoforms producing HA. HAS3 had been investigated in many cancers [16][17][18][19][20][21]38]. No study, however, has found consistent results of HAS3 effects on different cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…It is true that some studies have linked HAS3 to the promotion of tumor Fig. 3 Kaplan-Meier plots demonstrates the prognostic significances of HAS3 immunoexpression for diseasespecific survival and metastasisfree survival in UTUC (a, b) and UBUC (c, d), respectively growth or to overexpression in cancer compared to a normal organ [16,17,[19][20][21]. Contrariwise, other research has suggested that HAS3 is significantly reduced in premalignancy or malignancy compared to its benign counterparts [18,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation